The antimicrobial effect of edible film packaging in instant meatballs on Escherichia coli O157:H7 - Kavrut, E; Sezer, Ç (Journal of the Hellenic Veterinary Medical Society, 2024)
In this study, it is aimed to produce both edible films and antimicrobial that can be used as an alternative to plastic films that are mostly used in the market. The usability of whey protein isolate (WPI), which is an important and valuable side product in the field of dairy technology, in the production of edible natural film packaging material by formulating with additional components (glycerol, thyme essential oil (TO), zein, hibiscus extract and hibiscus tea) was investigated. The antimicrobial effects of the films on Escherichia coli O157: H7 were tested, and the effects of edible films and plastic films on the shelf life of meatballs were investigated. Analyzes (microbiological, chemical and sensory) of the prepared hamburger meatballs were performed on different days (0th, 3rd, 5th, 7th, 10 th and 12th) of storage (+ 4 oC). It was determined that all the edible films produced had an antimicrobial effect, the thyme groups extended the shelf life of meatballs by 7 days compared to the control group, and the other film groups provided a 5 days longer shelf life, again, compared to the control group. It was observed that especially the thyme-added groups degraded Escherichia coli O157: H7 at a rate of 2 logarithms (102) and the other groups at a rate of 1 logarithm. It has been determined that all natural films (except for zein 1% water) preserve their physical structure during the storage days (0th, 3rd, 5th, 7th, 10th and 12th) and do not add any undesirable quality to the meatballs.